Anticipated monetary policy and the dynamic behaviour of the term structure of interest rates - Jarkko Jääskelä; Jouko Vilmunen (Bank of Finland, 1999)
This paper investigates the measurement of anticipated interest rate policy and the effects of these expectations on the term structure of nominal interest rates.It is shown that, under the expectations hypothesis, the level of long-term interest rates depends on three factors: the level of the monetary policy interest rate, ie the steering rate; the spread between the market interest rate and the steering rate; and market expectations of the next steering rate change.The theoretical model builds on the assumption that market participants have only imperfect knowledge of the mechanism whereby changes in the steering rate are determined.As a consequence, expectations formation, although realistic, need not be entirely rational.Steering rate changes take the form of discrete jumps and occur infrequently on a daily scale.Given these assumptions, discussion of the determination of the term structure is related to the literature on uncertainty about monetary policy regimes and small samples, ie "peso" problems. Empirical analysis based on Nelson-Siegel estimates of the daily yield curves in Finland in the period 1 January 1993 to 31 October 1997 complements the theoretical discussion.The observed differences between estimated market expectations and actual tender rate changes are quite large in the sample, particularly for the longer maturities.The approach applied in this study is promising, not only in the sense of potentially providing estimates of market expectations concerning future discrete changes in monetary policy interest rates but also in the sense of its apparent potential in accounting for the often reported poor empirical performance of the expectations hypothesis.
URN:NBN:fi:bof-20140807123
Keywords: 330; term structure of interest rates; expectations; target changes; peso problems